Tradition Sraddha at The Grave Mbah Buyut Ki Sarengat to Improve The Character of Courtesy and Religiousness Students Lamongan Regency - Susandi, Ari; Muhammad, Devy Habibi; Andini, Nesi Anti; Irmaningrum, Rizka Novi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The tradition of sraddha at the tomb of Mbah Buyut Ki Sarengat is an activity that is often carried out every year in Tlanak Village, Kedungpring District, Lamongan Regency, which is held for three days starting on Rebo Kliwon, Kemis Legi, Friday Pahing. This tradition is carried out to express gratitude to Gusti Allah Almighty and to honor Mbah Buyut Ki Sarengat as the elder of Tlanak Village. The object of this study is to discuss the origins and procedures for implementing the tradition. The purpose of this study is to improve the courtesy and religious character of the Kedungpring Lamongan community. The results of the research on the nyadran tradition at the tomb of Mbah Buyut Ki Sarengat produced the origin of this tradition who was also a figure who spread Islam in Tlanak Village and could improve the courtesy and religious character of the students in Kedungpring Lamongan.